2022
DOI: 10.3389/fsurg.2022.845364
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of the Horizontal Calibrator in Correcting Leg Length and Restoring Femoral Offset in Total Hip Arthroplasty

Abstract: BackgroundLimb length discrepancy (LLD) is one of the most common postoperative complications and can cause serious consequences. Poor recovery of femoral offset (OD) will result in weakness of the patient's external rotator muscles and affect the patient's postoperative function. The study is aimed to present a simple approach that compensates for the shortcomings of previous measuring devices and combines the advantages of different measuring devices to provide more accurate limb length and femoral offset re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Chen et al designed a simple device with a pin and a spirit level to hold the leg in the same position during measurements. The authors reported a 2.5 mm LLD compared to traditional methods, which showed a 6.2 mm difference [13]. Another study compared three methods leg-to-leg comparison, a spiritlevel device, and a trochanter/joint ratio device.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al designed a simple device with a pin and a spirit level to hold the leg in the same position during measurements. The authors reported a 2.5 mm LLD compared to traditional methods, which showed a 6.2 mm difference [13]. Another study compared three methods leg-to-leg comparison, a spiritlevel device, and a trochanter/joint ratio device.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have previously examined the effectiveness of utilizing spirit-level devices to achieve leg parallelism during leg length measurements in THA [13,14]. Until March 2022, our center employed the conventional supraacetabular pin method and caliper measurement to correct leg length discrepancy based on preoperative radiographs.…”
Section: Introductionmentioning
confidence: 99%
“…The mean error of the measurements of the spherical marker centers’ angle using this software was less than 0.3° and the maximum error was 0.49°. Since both were less than 1 mm and 1°, respectively, this software can be considered to be as accurate as a “line gauge.” There have been previous reports testing the accuracy of implant-placement angles [ 27 ] and postoperative leg-length differences [ 28 ], but these have mainly been reported in 1.0° and 1.0 mm increments. Therefore, the mean error in this study was 0.3° and 0.3 mm, and such an error of less than 1° and 1 mm is sufficiently accurate.…”
Section: Discussionmentioning
confidence: 99%
“…Por su parte, Chen y cols. 19 también lograron un aumento del offset femoral con el uso de un calibre intraoperatorio, pero sin significancia estadística con respecto al grupo de control.…”
Section: Análisis Estadísticounclassified